Diblock and Random Antifouling Bioactive Polymer Brushes on Gold Surfaces by Visible‐Light‐Induced Polymerization (SI‐PET‐RAFT) in Water. Issue 3 (13th December 2021) - Kuzmyn, Andriy R.; Teunissen, Lucas W.; Fritz, Pina; van Lagen, Barend; Smulders, Maarten M. J.; Zuilhof, Han
Abstract: Surface‐initiated photoinduced electron‐transfer‐reversible addition–fragmentation chain transfer (SI‐PET‐RAFT) is, for the first time, used for the creation of antifouling polymer brushes on gold surfaces based on three monomers: oligo(ethylene glycol) methyl ether methacrylate (MeOEGMA), N ‐(2‐hydroxypropyl) methacrylamide (HPMA), and carboxybetaine methacrylamide (CBMA). These coatings are subsequently characterized by X‐ray photoelectron spectroscopy (XPS) and ellipsometry. The living nature of this polymerization allows for the creation of random and diblock copolymer brushes, which are based on HPMA (superb antifouling) and CBMA (good antifouling and functionalizable via activated ester chemistry). The polymer brushes demonstrate good antifouling properties against undiluted human serum, as monitored by quartz crystal microbalance with dissipation (QCM‐D) and surface plasmon resonance (SPR) spectroscopy in real time. The amount of immobilization of bioactive moieties, here an antibody immobilized using N ‐succinimidyl ester–1‐ethyl‐3‐(3‐dimethylaminopropyl)carbodiimide hydrochloride (NHS–EDC) coupling, in the diblock and random copolymer brushes is monitored by SPR, and is analyzed with respect to the brush structure, and is shown to be superior in the diblock copolymer brush. This approach represents a scalable, robust, mild, oxygen‐tolerant, and heavy‐metal‐free route toward the production of antifouling and functional copolymer brushes (on gold surfaces) that open up applications in biosensing and tissue engineering. Abstract : Diblock and random copolymer brushes based on N ‐(2‐hydroxypropyl) methacrylamide (HPMA) and carboxybetaine methacrylamide (CBMA) on gold surfaces are created by visible‐light‐triggered oxygen‐tolerant polymerization. Such brushes are highly antifouling upon exposure to undiluted human serum and can be efficiently functionalized with antibodies. The application of such coatings is envisioned in biosensing devices and tissue engineering.